Integrasi Nilai HRM dan Kapabilitas Inovasi Teknologi terhadap Keunggulan Kompetitif dan Pengembangan Organisasi Perbankan Syariah - Pipit Sundari; Satria Avianda Nurcahyo; Yeni Indraningtyas; Ahmad Ali; Teguh Harso Widagdo (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2026)
This study explores the influence of Human Resource Management (HRM) Values ​​and Technological Innovation Capability on Competitive Advantage and Organizational Development in the Islamic banking sector in Central Java. In the context of increasing industry competition and accelerating digital transformation, the integration of effective HRM and strategic technological innovation is considered crucial to strengthening organizational competitiveness and sustainability. Quantitative research methods were applied through a survey of 250 Islamic bank employees, using purposive sampling to target relevant respondents. Data analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS) tested construct validity and reliability, as well as the interrelationships between variables. The findings indicate that HRM Values ​​and Technological Innovation Capability have a significant positive influence on Competitive Advantage and Organizational Development, with Competitive Advantage partially mediating the relationship between HRM, technological innovation, and organizational development. This study confirms the strategic role of HRM and technological innovation in sustainably improving organizational performance and provides both theoretical contributions and practical implications for Islamic banking institutions in formulating organizational development strategies based on competitive advantage and digital transformation.   Abstrak Penelitian ini mengeksplorasi pengaruh Nilai HRM dan Kapabilitas Inovasi Teknologi terhadap Keunggulan Kompetitif dan Pengembangan Organisasi di sektor perbankan syariah di Jawa Tengah. Dalam konteks persaingan industri yang meningkat dan percepatan transformasi digital, integrasi HRM yang efektif dan inovasi teknologi strategis dianggap krusial untuk memperkuat daya saing dan keberlanjutan organisasi. Metode penelitian kuantitatif diterapkan melalui survei terhadap 250 karyawan bank syariah, dengan purposive sampling untuk menargetkan responden yang relevan. Analisis data menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS) menguji validitas dan reliabilitas konstruk, serta pengaruh antar variabel. Temuan menunjukkan bahwa Nilai HRM dan Kapabilitas Inovasi Teknologi memiliki pengaruh positif signifikan terhadap Keunggulan Kompetitif dan Pengembangan Organisasi, dengan Keunggulan Kompetitif memediasi sebagian hubungan antara SDM, inovasi teknologi, dan pengembangan organisasi. Studi ini menegaskan peran strategis SDM dan inovasi teknologi dalam meningkatkan kinerja organisasi secara berkelanjutan dan menyediakan kontribusi teoritis sekaligus implikasi praktis bagi lembaga perbankan syariah dalam merumuskan strategi pengembangan organisasi berbasis keunggulan kompetitif dan transformasi digital.